Characterization of the complete chloroplast genome of Actinidia Melanandra (Actinidiaceae). Issue 2 (3rd July 2019) - Zhao, Yuemei; Zhao, Zhixin; Tang, Weili; Li, Xiaoling; Zhao, Yongping; Gao, Baoyun; Xie, Xiaodan; Zhang, Xiaobin
Abstract: The whole chloroplast (cp) genome sequence of Actinidia melanandra has been characterized from Illumina pair-end sequencing. The complete cp genome was 156, 124 bp in length, containing a large single-copy region (LSC) of 88, 006 bp and a small single-copy region (SSC) of 20, 332 bp, which were separated by a pair of inverted repeat (IR) regions of 23, 893 bp. The genome contained 131 genes, including 84 protein-coding genes, 39 tRNA genes, and 8 ribosomal RNA genes (4 rRNA species). Most genes occur as a single copy, while 17 gene species are duplicated. Phylogenetic analysis revealed that A. melanandra is closely related to the species of A. deliciosa and A. chinensis.